Philosophical foundation of education - Bhattacharya, Srinibas (Delhi : Atlantic publisher, 2008)
From the dawn of civilization, man has been marching in search of wisdom. Various experiments are projected through education, so that humanity, happiness and harmony be wedded together. Education is indispensable for making life and living meaningful and purposive. Its significance cannot be fully appreciated unless it is looked at in proper perspectives$1 (Bphilosophical, sociological and psychological. The philosophical perspectives provide the basis of education in terms of values, aims and objectives. Without a philosophical basis, education tends to lose its direction. In addition, philosophy provides a framework within which education and educational problems can be discussed. Above all, the nature of decisions is significantly determined by philosophy and education. A philosophy of education is often adequate to make immediate resolution to conflicts. Thus, philosophy of education is a comprehensive area of knowledge with an interdisciplinary approach. Keeping in view the significant bearing of philosophical basis of education on life and society, The present book philosophical foundation of education has been written. It is an in-depth study of all the aspects related to education. Beginning with the philosophical foundation of education, The book analytically discusses education in relation to issues of human values, freedom and discipline, peace and democracy and its application in classroom teaching. It also acquaints the readers with the Indian philosophy of education. Apart from these, it analytically presents the aims, creativity, role and human factors of education. Here, the Indian Standard of education has been particularly studied. It is hoped that the present book will prove immensely useful for the students and teachers of both education and philosophy. Even the General readers will find it highly informative.s
Keywords: Education -- Philosophy